The need to articulate a coherent non-verbal and paraverbal discourse in the classroom - Al Shehri, Hamdan (Avances en Supervisión Educativa, 2012)
The importance of employing non-verbal immediacy behaviours consistently in the classroom.Mounting research findings demonstrate that one of the decisive factors to be taken into consideration within the current peer learning, affecting team building training, are definitely non-verbal immediacy behaviours. This theoretical article analyses current major categories and factors of non-verbal immediacy behaviours in classroom, in order to provide a better understanding and action-oriented coherence.
Keywords: multidisciplinary; discourse; learning; paratextual; gesture